2017
DOI: 10.1177/1077559517701855
|View full text |Cite
|
Sign up to set email alerts
|

Children Placed In Out-of-Home Care as Midlife Adults: Are They Still Disadvantaged or Have They Caught Up With Their Peers?

Abstract: International research has consistently reported that children placed in out-of-home care (OHC) have poor outcomes in young adulthood. Yet, little is known about their outcomes in midlife. Using prospective data from a cohort of more than 14,000 Swedes born in 1953, of which nearly 9% have been placed in OHC, this study examines whether there is developmental continuity or discontinuity of disadvantage reaching into middle age in OHC children, compared to same-aged peers. Outcome profiles, here conceptualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 48 publications
4
22
0
1
Order By: Relevance
“…Recently published studies emphasize the vulnerability of children placed in foster care, both as a result of early life circumstances but also since foster care placement in itself may be a risk factor for health problems in childhood [ 58 60 ]. Furthermore, even though the aim of an out-of-home placement is to provide children from adverse birth homes with better opportunities, these individuals constitute a group with a particular high risk of negative long term outcomes [ 19 , 20 ]. Former foster youth also experience increased risks of homelessness, low educational attainment and unemployment [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published studies emphasize the vulnerability of children placed in foster care, both as a result of early life circumstances but also since foster care placement in itself may be a risk factor for health problems in childhood [ 58 60 ]. Furthermore, even though the aim of an out-of-home placement is to provide children from adverse birth homes with better opportunities, these individuals constitute a group with a particular high risk of negative long term outcomes [ 19 , 20 ]. Former foster youth also experience increased risks of homelessness, low educational attainment and unemployment [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the pronounced aim is to provide the child with better opportunities for development than in an adverse home environment. Even though the aim of an out-of-home placement is to provide these children with better opportunities, childhood experience of out-of-home care seems to be one of the strongest markers for compromised long-term health and psychosocial development that we know of [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children growing up in out-of-home care, such as those living in welfare homes, may have higher risks of adverse physical, emotional, and behavioral-related outcomes, which may further elevate risks of unstable life-course trajectories in later adulthood life [17,18,19,20]. As compared to children in the general population, children living in welfare homes have higher rates of chronic health conditions (CHCs) [21], including mental retardation and malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…We may, for example, place a child in out-of-home care and thereby solve the immediate problem of needing to protect a child who has been exposed to violence, abuse and neglect. At the same time, decades of research have shown that many children and young people who have grown up in the care system have a greater likelihood of poorer educational attainment and mental ill-health (Dill et al 2012;Österberg, Gustafsson, and Vinnerljung 2016;Brännström et al 2017;Maclean, Taylor, and O'Donnell 2017). However, we cannot say unquestionably that the care placement itself causes these kinds of poor outcomes.…”
Section: Resultsmentioning
confidence: 98%